Testing of fundamental indicators over the long term on the U.S. stock market - Perlác, Radovan; Musílek, Petr, 1965-; Drahokoupil, Matěj; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
The goal of this master’s thesis was to analyze whether fundamental indicators could identify securities with the potential to outperform the U.S. stock market during the time period 2014 - 2024. The study is divided into a theoretical and an experimental part. The theoretical part explores the financial discipline of fundamental analysis, explaining the concept of fundamental indicators and their significance. The experimental part first outlines the methodology which is then used for testing of the seven chosen fundamental indicator based strategies against the S&P 100 index, as our set benchmark. Among these strategies, only the one emphasizing high ROE stocks consistently outperformed the benchmark. Strategies focusing on the low P/E ratio stocks, as well as combined strategies involving stocks with both low P/S ratio and high ROE, or low P/E ratio and high ROE, were successful in surpassing the benchmark under certain conditions, particularly when focusing on stricter values of fundamental indicators. Conversely, strategies centered on low P/S ratio stocks, low P/BV stocks, and high dividend yield stocks failed to outperform the benchmark throughout the studied period.
Vedoucí práce: Petr Musílek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses